Role of neural factors in the regulation of acetylcholinesterase expression in mammalian skeletal muscle cells. - Boudreau-Larivière, Céline. (University of Ottawa (Canada), 1999)
Neural signals modulate acetylcholinesterase (AChE) expression in skeletal muscle cells. However, the cellular and molecular events mediating these effects are poorly understood. The mechanisms by which nerve-evoked electrical activity and nerve-derived trophic factors regulate the expression of AChE along muscle fibers was therefore elucidated. The contribution of nerve-evoked activity versus intrinsic properties of muscle fibers was assessed for their role in dictating the distinct patterns of AChE expression displayed by fast and slow muscles. We demonstrate that nerve-evoked electrical impulses play a key role in regulating AChE synthesis in these distinct muscle types. We also demonstrate that myogenic precursor cells from fast and slow muscle fibers generate myotubes that display similar patterns of AChE expression. Together, these findings suggest that nerve-evoked electrical activity rather than intrinsic properties of muscle cells is the primary regulator of AChE expression in fast and slow muscles. The importance of transcriptional versus post-transcriptional mechanisms in mediating the activity-dependent regulation of AChE was also determined. We demonstrate that higher levels of AChE mRNA observed in fast versus slow muscles is due to post-transcriptional events. We also show that reductions of AChE mRNA seen in mature denervated muscles cannot be accounted for by a decrease in the rate of AChE gene transcription. Denervation-induced reductions in the levels of AChE mRNA were less pronounced in muscles of developing animals. This attenuated decrease in AChE transcript abundance may be due to a transient enhancement in the transcriptional activity of the AChE gene observed in denervated muscles of developing rats. Transcriptional as well as post-transcriptional mechanisms are therefore important in mediating the activity-dependent regulation of AChE in developing muscles whereas post-transcriptional events are the primary mediators controlling AChE expression in mature muscles. Finally, the activity of several rat AChE promoter fragments in synaptic versus extrasynaptic regions of muscle fibers was assessed to determined whether enhanced transcription of the AChE gene in synaptic nuclei contributes to the accumulation of AChE transcripts at the neuromuscular synapse. Our findings indicate that synapse-specific activity of the AChE gene contributes to localized expression of the enzyme and its mRNA at the neuromuscular junction. Furthermore, we observed that calcitonin gene-related peptide (CGRP) and ciliary neurotrophic factor (CNTF) downregulate AChE expression. The suppressive effects of CGRP and CNTF on AChE expression suggest that a combination of activating and inhibiting signalling cascades may function in concert to regulate the abundance of AChE transcripts at synaptic sites.
Keywords: Biology, Molecular.